Long-term drying shrinkage of self-compacting concrete: Experimental and analytical investigations. (30th March 2019) - Abdalhmid, Jamila M.; Ashour, A.F.; Sheehan, T.
Highlights: Experimental results of long-term drying shrinkage strains of self-compacting concrete (SCCs) presented. Experimental results of drying shrinkage were compared to five existing models. Drying shrinkage of SCCs containing FA was considerably lower than that of the control concrete. Among all models studied, ACI 209R-92 provided the best prediction of drying shrinkage compared to the other models Abstract: The present study investigated long-term drying shrinkage strains of self-compacting concrete (SCCs). For all SCCs mixes, Portland cement was replaced with 0–60% of fly ash (FA), fine and course aggregates were kept constant with 890 kg/m 3 and 780 kg/m 3, respectively. Two different water binder ratios of 0.44 and 0.33 were examined for both SCCs and normal concrete (NCs). Fresh properties of SCCs such as filling ability, passing ability, viscosity and resistance to segregation and hardened properties such as compressive and flexural strengths, water absorption and density of SCCs and NCs were also determined. Experimental results of drying shrinkage were compared to five existing models, namely the ACI 209R-92 model, BSEN-92 model, ACI 209R-92 (Huo) model, B3 model, and GL2000. To assess the quality of predictive models, the influence of various parameters (compressive strength, cement content, water content and relative humidity) effecting on the drying shrinkage strain as considered by the models are studied. The results showed that, using up to 60% of FA as cement replacement can produce SCC with a compressive strength as high as 30 MPa and low drying shrinkage strain. SCCs long-term drying shrinkage from 356 to 1000 days was higher than NCs. ACI 209R-92 model provided a better prediction of drying shrinkage compared with the other models.